1997
DOI: 10.1074/jbc.272.7.4079
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of Epidermal Growth Factor Receptors during Activation and Endocytosis

Abstract: Mutation of the autophosphorylation sites of receptor protein-tyrosine kinases alters ligand dependent internalization and down-regulation, indicating a critical role for these sites in receptor processing. Currently, no differences in receptor processing based on an individual autophosphorylation site have been defined. By using a glutathione S-transferase fusion protein containing the src homology 2 domains of phospholipase C-␥ 1 to specifically recognize tyrosine 992 on the EGF receptor (Tyr(P) 992 ), we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Previous reports as well as our current study (Figures 2a-c) suggest that the binding of ouabain or TCTP to the Na,K-ATPase a subunit stimulates Src-mediated EGFR phosphorylation, resulting in phosphorylation of other tyrosine residues on EGFR independent of serum (Haas et al, 2002;Kometiani et al, 2005;Kim et al, 2009). Phosphorylation of Tyr992 on EGFR has been reported to result in activation of PLC-g-mediated downstream signaling (Emlet et al, 1997) and phosphorylation of a pair of tyrosines 1148 and 1173, providing a docking site for scaffold proteins such as Shc, involved in the MAP kinase signaling pathway (Zwick et al, 1999). Here, we demonstrated TCTP-induced phosphorylation of Tyr992, Tyr1148 and Tyr1173 of EGFR (Figure 2d), attraction of adaptor proteins to the phosphorylated EGFR (Figure 3a), activation of the Ras-Raf-MEK-ERK1/2 pathway ( Figure 3b) and phosphorylation of PLC-g (Figure 3d).…”
Section: Discussionsupporting
confidence: 80%
“…Previous reports as well as our current study (Figures 2a-c) suggest that the binding of ouabain or TCTP to the Na,K-ATPase a subunit stimulates Src-mediated EGFR phosphorylation, resulting in phosphorylation of other tyrosine residues on EGFR independent of serum (Haas et al, 2002;Kometiani et al, 2005;Kim et al, 2009). Phosphorylation of Tyr992 on EGFR has been reported to result in activation of PLC-g-mediated downstream signaling (Emlet et al, 1997) and phosphorylation of a pair of tyrosines 1148 and 1173, providing a docking site for scaffold proteins such as Shc, involved in the MAP kinase signaling pathway (Zwick et al, 1999). Here, we demonstrated TCTP-induced phosphorylation of Tyr992, Tyr1148 and Tyr1173 of EGFR (Figure 2d), attraction of adaptor proteins to the phosphorylated EGFR (Figure 3a), activation of the Ras-Raf-MEK-ERK1/2 pathway ( Figure 3b) and phosphorylation of PLC-g (Figure 3d).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, while a proportion of PI3K-C2␣ was present in phosphotyrosine complexes within minutes, this PI3K isozyme accumulated over a much longer period, about 20 to 40 min, following ligand addition. This difference suggests either differential compartmentalization of the class II PI3K isozymes or a difference in (17,29). EGF stimulation of PI3K activity has been described for a large number of primary cells and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that EGF treatment promotes the translocation of EGFR from the cell membrane to the perinuclear membrane and nucleus (Emlet et al, 1997;Hsu and Hung, 2007). This nuclear shuttling depends on a novel tripartite type of nuclear localization signal localized in the juxta-membrane domain of EGFR (Hsu and Hung, 2007).…”
Section: Galectin-3 Promotes Muc1 and Egfr Endocytosis J Merlin Et Almentioning
confidence: 96%